Plasticity in the Auditory System - Irvine, Dexter (Elsevier B.V., 2017)
Over the last 30 years a wide range of manipulations of auditory input and experience have been shown to result in plasticity in auditory cortical and subcortical structures. The time course of plasticity ranges from very rapid stimulus-specific adaptation to longer-term changes associated with, for example, partial hearing loss or perceptual learning. Evidence for plasticity as a consequence of these and a range of other manipulations of auditory input and/or its significance is reviewed, with an emphasis on plasticity in adults and in the auditory cortex. The nature of the changes in auditory cortex associated with attention, memory and perceptual learning depend critically on task structure, reward contingencies, and learning strategy. Most forms of auditory system plasticity are adaptive, in that they serve to optimize auditory performance, prompting attempts to harness this plasticity for therapeutic purposes. However, plasticity associated with cochlear trauma and partial hearing loss appears to be maladaptive, and has been linked to tinnitus. Three important forms of human learning-related auditory system plasticity are those associated with language development, musical training, and improvement in performance with a cochlear implant. Almost all forms of plasticity involve changes in synaptic excitatory - inhibitory balance within existing patterns of connectivity. An attractive model applicable to a number of forms of learning-related plasticity is dynamic multiplexing by individual neurons, such that learning involving a particular stimulus attribute reflects a particular subset of the diverse inputs to a given neuron being gated by top-down influences. The plasticity evidence indicates that auditory cortex is a component of complex distributed networks that integrate the representation of auditory stimuli with attention, decision and reward processes.
Keywords: Attention; Hearing loss; Neuromodulators; Perceptual learning; Stimululs-specific adaptation; Synaptic weights